Prevalence of and risk factors associated with latent tuberculosis in Singapore: A cross-sectional survey. (July 2018) - Yap, Peiling; Tan, Kristin Hui Xian; Lim, Wei Yen; Barkham, Timothy; Tan, Linda Wei Lin; Chen, Mark I-Cheng; Wang, Yee Tang; Chee, Cynthia Bin Eng
Highlights: An overall latent tuberculosis prevalence of 12.7% was found amongst Singapore residents. There was a wide variation in positivity rate based on the participants' country of birth. Risk factors include age, education, socio-economic status, and alcohol usage. Abstract: Objectives: This first cross-sectional survey on latent tuberculosis infection (LTBI) in Singapore was performed by utilizing the QuantiFERON Gold In-tube (QFT-GIT) assay to collect data on the prevalence of LTBI and to identify potential risk factors associated with LTBI. Methods: Nationwide household addresses were selected randomly for enumeration, and Singaporeans or Permanent Residents aged 18–79 years were identified. One eligible member per household was selected using the Kish grid. Each participant answered a questionnaire assessing their medical history (including tuberculosis (TB)), socio-economic factors, and lifestyle factors. They also provided a blood specimen for the QFT-GIT assay. Participants with a positive QFT-GIT result were defined as having LTBI if they were asymptomatic. To identify independent risk factors, adjusted hazard ratios were obtained using the multivariable modified Breslow–Cox proportional hazards model. Results: An overall QFT-GIT positivity rate of 12.7% was detected amongst 1682 Singapore residents. There was a wide variation in the positivity rate according to the participants' country of birth. Higher LTBI prevalence was also significantly associated with increasing age, lower educational and socio-economic status, and alcohol use. Conclusions: Given the high prevalence of LTBI amongst foreign-born residents from regional countries, similar studies should be conducted amongst migrants in Singapore to improve national guidelines on screening and preventive treatment against LTBI.